LIFE PATTERN OF GASTROPODS ON BREAKWATER AND SANDY BEACH ECOSYSTEM IN WATER CONSERVATION AREA PARIAMAN CITY WEST SUMATRA PROVINCE - Romanta A. Tamba; Afrizal Tanjung; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was carried out on the breakwater rocks in Water Conservation AreaPariaman West Sumatra Province in May 2013. The goal in conducting this study is tofind out how to survive gastropods in breakwater and sandy beach ecosystems areconstantly subjected to pressure waves. The method used was a survey method thatdirectly observe the behavior and movement of gastropods.There are 5 types of gastropods which have distinctive way of life to survive inthe face of pressure waves. Gastropods movement in the face of pressure waves in thesubmerged breakwater when high tide and exposed to the atmosphere when the low tidesas well as having an active movement, slow and settled. Life pattern gastropods in thesandy habitat gastropods will be attached to rock fragments and other fossil biota. Therewas slow movement that occurs when the wave came. Human impact on the gastropodswill always avoided by attaching themselves to the substrate tightly, closing their shellimmediately and move quickly. Gastropods movement in rock breakwater depends on thecause as something approaching movement (humans and other organisms), exposure tofree air (drought) and the most important is the availability of food.Keywords: Gastropods, survive, breakwaters, pressure waves, West Sumatera